DEVELOPING ENTREPRENEURIAL MINDSET THROUGH THE 'YOUNG LELEPRENEUR' COLLABORATIVE LEARNING MODEL AND CURRICULUM INTEGRATION AT CENDERAWASIH II SENIOR HIGH SCHOOL - Rusdiyanto, Edi; Soesanta, Prabawa Eka; Muna, Siti Umamah Naili; Munawir, Abdillah (LPPM Univ. Ibn Khaldun Bogor, 2025)
SMA Cenderawasih II in South Tangerang faces dual challenges, including students’ low understanding of nutrition and the economic limitations of their families. The Community Service Team from the Graduate School (SPS) of Universitas Terbuka (UT) took the initiative to implement a collaborative learning model called